DIGITAL DATA SECURITY WITH APPLICATION OF CRYPTOGRAPHY AND DATA COMPRESSION TECHNIQUES - Kuncoro, Adam Prayogo; Mustofa, Dinar; Krisbiantoro, Dwi; Tarwoto, Tarwoto (Informatika, Universitas Jenderal Soedirman, 2023)
The need for digital data security is to ensure that the data and information we have are confidential and can only be accessed by authorized users. And no one can change the information in it, thus ensuring complete accuracy. The functions of data security are confidentiality, authentication, integrity, and anti-repudiation. Compression techniques are used to protect digital data because they aim to make less storage space and allow us to transfer more data over the internet. This study aims to plan to prove the application of a combination of 2 (two) techniques, namely compression and cryptography to digital data with the aim of increasing the security of the data. This research has the result that the compression technique of the Huffman method is the most effective in compressing digital data into the smallest file size compared to other compression methods. It can compressed the data size by around 30% (thirty percent) to 40% (forty percent) compared to the original data size. And coupled with data security with cryptographic encryption techniques so that files remain safe when transferred over the network.